(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
OBJECTIVES: The aim of the present investigation was to form matrix patches with ethyl cellulose (EC) as the base polymer, polyvinyl pyrrolidone (PVP) as the copolymer, plasticizer with dibutyl phthalate (DBP) or acetyl tributyl citrate (ATBC) and the drug glipizide (gz) by the solvent casting method. Physicochemical properties of the patches and in vitro drug release were determined in a modified Keshary-chien diffusion cell to optimize the patch formulations with the help of experimental data and figures for further studies. TECHNIQUES: EC and PVP of different proportions with different weight percentages of either DBP or ATBC and a fixed amount of glipizide were taken for matrix patch formations. The dried patches were used for measuring their drug contents as well as their thicknesses, tensile strengths, moisture contents and water absorption amounts in percentage. In vitro release amounts at different intervals were measured by UV-spectrophotometer. RESULTS: Drug contents varied from 96 - 99%. Thickness and tensile strength varied due to weight variation of the ingredients in the matrix patches. Moisture content and water absorption in wt % were greater for the patches containing higher amount of PVP due to its hydrophilic nature. Variations in drug release were observed among various formulations. It was found that all of the releases followed diffusion controlled zero order kinetics. Two DBP patches yielded better and more adequate release. CONCLUSIONS: The two formulations with DBP were the preferred choice for making matrix patches for further studies.